2014
DOI: 10.1074/jbc.m114.554147
|View full text |Cite
|
Sign up to set email alerts
|

Interferon γ-inducible Protein (IFI) 16 Transcriptionally Regulates Type I Interferons and Other Interferon-stimulated Genes and Controls the Interferon Response to both DNA and RNA Viruses

Abstract: Background: IFI16 binds dsDNA and elicits a type I interferon response. Results: IFI16 knockdown cells show a decrease in interferon production and ISG expression in response to DNA and RNA ligands and cyclic dinucleotides. Conclusion: IFI16 transcriptionally regulates ISGs to enhance IFN responses to multiple IFN-inducing ligands.Significance: IFI16 has a broader role in the regulation of ISG expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 47 publications
9
115
0
Order By: Relevance
“…It does so by interacting with the transcription factor Sp1, displacing it from promoters, thereby leading to a decrease in HCMV DNA synthesis, a decrease in viral gene expression and inhibition of viral replication [25]. Furthermore, IFI16 has recently been shown to be required for gene induction in response to innate immune RNA and DNA detection, since IFI16 is required for optimal RNA polymerase II occupancy on IFN-a and Immune Stimulated Gene (ISG) promoters [26]. This provides evidence for a role for IFI16 in transcriptional regulation and reveals a direct antiviral role for IFI16 to both DNA and RNA viruses.…”
Section: Early Research On the Human Pyhinsmentioning
confidence: 99%
“…It does so by interacting with the transcription factor Sp1, displacing it from promoters, thereby leading to a decrease in HCMV DNA synthesis, a decrease in viral gene expression and inhibition of viral replication [25]. Furthermore, IFI16 has recently been shown to be required for gene induction in response to innate immune RNA and DNA detection, since IFI16 is required for optimal RNA polymerase II occupancy on IFN-a and Immune Stimulated Gene (ISG) promoters [26]. This provides evidence for a role for IFI16 in transcriptional regulation and reveals a direct antiviral role for IFI16 to both DNA and RNA viruses.…”
Section: Early Research On the Human Pyhinsmentioning
confidence: 99%
“…There may be indirect effects, however, when stable knockdown cells are studied. Thompson et al recently reported that in long-term depletion experiments, loss of IFI16 leads to a decrease in IFN responses to multiple agents, including DNA and RNA viruses (10). Therefore, further studies are needed to fully define the functions of cGAS and IFI16.…”
Section: Roles For Both Ifi16 and Cgas In Innate Responses In Transfementioning
confidence: 99%
“…The Pyrin and HIN-containing interferon γ-inducible protein 16 (IFI16) protein, initially described as a cytosolic DNA sensor (5), has been demonstrated to be nuclear in many cells and to promote the activation of inflammasomes (6, 7) and production of IFNs (8,9) in response to herpesvirus infection. These initial studies involved short-term siRNA depletion of IFI16; in addition, a recent study showed that long-term knockdown of IFI16 expression led to abrogated IFN responses to not only DNA viruses, such as herpes simplex virus (HSV), but also RNA viruses, such as Sendai virus (10).…”
Section: Virus-host Interactionsmentioning
confidence: 99%
“…Since then, data supporting a role for IFI16 in DNA sensing, STING activation, inflammasome activation, genome silencing, and gene expression have been reported (25,26,31,62,63; for a recent review and discussion of the literature on IFI16 in DNA sensing and genome regulation, see reference 23). The focus here is on IFI16 in the STING pathway.…”
Section: Interactions Between the Cgas-cgamp-sting Pathway And Other mentioning
confidence: 99%